Chemo-, regio- and stereo-selective aerial oxidation of limonene to the endo-1,2-epoxide over Mn(Salen)-sulfonated SBA-15 - Saikia, Lakshi; Srinivas, D.; Ratnasamy, Paul (Applied Catalysis A-General, 2006)
Mn(Salen) complexes immobilized on sulfonic acid-functionalized SBA-15 molecular sieves (SBA-15-pr-SO3-Mn(Salen)) catalyze the Mukaiyama-type oxidation of R-(+)-limonene selectively to the 1,2-epoxide with molecular oxygen at 298 K (Salen = N,N-ethylenebis(salicylidenaminato)). The endo-diastereomer is formed with a diasteromeric excess of 39.8%. This catalyst exhibited higher catalytic activity than ``neat'' Mn(Salen) complexes directly supported on SBA-15 or zeolite-Y. A change in the oxidation state of Mn from +3 in the ``neat'' complex to +2 when immobilized on the sulfonated surface is a probable cause for the observed enhancement of catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: aerial oxidation of limonene; catalysis by Mn(Salen) complexes; chemo-; immobilized Mn Schiff base complexes; Mesoporous molecular sieves; Mukaiyama-type oxidation; regio- and stereo-selective epoxidation; sulfonic acid-functionalized SBA-15

Activation and reactivity of epoxides on solid acid catalysts - Saikia, Lakshi; Satyarthi, J. K.; Srinivas, Darbha; Ratnasamy, P. (Journal of Catalysis, 2007)
The aminolysis of epoxides over novel solid catalysts (Bronsted-acidic SBA-15 functionalized with propylsulfonic acid and Lewis-acidic Ti-MCM-41) is reported. The acidic properties of these catalysts were determined by FTIR spectroscopy and temperature-programmed desorption of pyridine and NH3, respectively. The mesoporous solid acids of the present study are reusable and exhibit significantly higher catalytic activities than known catalysts for opening of the oxirane ring with nitrogen (aromatic and aliphatic amines)-containing and oxygen (alcohols)-containing nucleophiles. A range of beta-amino, alcohols with high regioselectivity and stereoselectivity were synthesized. Adsorption studies as well as the sigmoid shape of the conversion- versus-time plots show that the epoxide and amine compete for adsorption on the acidic sites (-SO3H or Ti4+) on the catalyst surface. Epoxide adsorption and activation on acid sites are the more critical processes. Catalytic activity decreases with increasing basicity of the amines and/or the alcohol, as well as the dielectric constant of the solvent. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: aminolysis and alcoholysis of epoxides; beta-Amino alcohols; ring opening of epoxides; SBA-15 functionalized with propylsulfortic acid; Solid acids; Ti-MCM-41

Regio- and stereoselective synthesis of beta-amino alcohols over titanosilicate molecular sieves - Satyarthi, Jitendra K.; Saikia, Lakshi; Srinivas, Darbha; Ratnasamy, P. (Applied Catalysis A-General, 2007)
A novel application of titanosilicate molecular sieves in the synthesis of P-amino alcohols via aminolysis of epoxides, at mild and solvent-free conditions, is reported, for the first time. A range of beta-amino alcohols with nearly 100% regio- and stereoselectivity was produced over these reusable solid catalysts in high yields. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Aminolysis of epoxides; synthesis of beta-amino alcohols; Ti-MCM-41; titanosilicate molecular sieves

Active sites in vanadia/titania catalysts for selective aerial oxidation of beta-picoline to nicotinic acid - Srinivas, Darbha; Hoelderich, Wolfgang F.; Kujath, Steffen; Valkenberg, Michael H.; Raja, Thirumalaiswamy; Saikia, Lakshi; Hinze, Ramona; Ramaswamy, Veda (Journal of Catalysis, 2008)
Vanadia/titania catalysts with varying vanadium content were prepared by impregnation using three different titania carrier materials of varying surface area, The structure of active vanadium species for beta-picoline oxidation was investigated. Vanadium is mainly in the +5 oxidation state as revealed by electron paramagnetic resonance (EPR) and V-51 magic-angle spinning nuclear magnetic resonance (V-51 MAS NMR) spectroscopy techniques. Diffuse reflectance UV-visible (DRUV-vis) spectroscopy and spectral deconvolution enabled identification of at least five different types of vanadium oxide species in these catalysts: monomeric tetrahedral VO43-, polymeric distorted tetrahedral VO3-, square pyramidal V2O5, octahedral V2O62- and V4+ oxide species. While both VO43- and VO3- species are active in beta-picoline oxidation, the latter having a distorted tetrahedral geometry yielded the desired products-picolinaldehyde and nicotinic acid. High surface area, anatase structure for the support and dispersed, distorted tetrahedral vanadium oxide species are the key parameters determining the activity and selectivity of these oxidation catalysts. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Active vanadium species; Nicotinic acid; Oxidation of beta-picoline; Selective aerial oxidation; Spectroscopic investigations; Vanadia/titania

Double metal cyanides as efficient solid acid catalysts for synthesis of beta-amino alcohols under solvent-free conditions - Saikia, Lakshi; Satyarthi, J. K.; Gonnade, Rajesh G.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2008)
A novel application of Fe-Zn double metal cyanide complexes as solid, acid catalysts for regioselective synthesis of beta-amino alcohols under solvent-free conditions via ring-opening of epoxides with amines is reported for the first time. The conversion of epoxides to beta-amino alcohols is nearly 100%. In the reaction with styrene oxide, regioselective beta-amino alcohol formation is higher with aromatic than with aliphatic amines. Strong Lewis acidic Zn(2+) ions in the catalyst are probably the active sites in this reaction.
Keywords: beta-Amino alcohols; double metal cyanide (DMC); regioselective ring-opening of epoxides; Single crystal x-ray structure; solid Lewis-acid catalyst

Functionalized SBA-15 and its catalytic applications in selective organic transformations - Srinivas, Darbha; Saikia, Lakshi (Catalysis Surveys from Asia, 2008)
Ordered, mesoporous SBA-15 functionalized with organic and inorganic moieties exhibits efficient catalytic activity in a variety of organic transformations. In this account, reviewing our own work, three-sets of surface-modified SBA-15 materials have been investigated. The first-set of materials consists of SBA-15 modified with organo-acidic (propyl thiol and propyl sulfonic acid) and basic (propyl amine and propyl adenine) moieties. The second-set of materials was prepared by grafting Mn complexes to the organo-functionalized SBA-15. The third-set composes of nanocrystalline metal oxides supported on SBA-15. All these catalysts have been characterized by structural and spectroscopic techniques. Catalytic activities of the first-set of solid materials have been investigated in acid/base-catalyzed reactions viz., ring-opening of epoxides with amines (producing beta-amino alcohols), esterification, three-component-Mannich reactions and cycloaddition of CO(2) to epoxides. The Mn complexes grafted on organofunctionalized SBA-15 are efficient catalysts for the chemo-, regio- and stereoselective aerial oxidation of monoterpenes at ambient conditions. TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 catalyzed biomimetic oxyhalogenation of aromatic compounds. In all these reactions, the functionalized SBA-15 showed high selectivity.
Keywords: grafted Mn-Salen complexes; Ordered mesoporous silica; organofunctionalized SBA-15; oxidation catalysts; Oxyhalogenation of aromatics

Redox and selective oxidation properties of Mn complexes grafted on SBA-15 - Saikia, Lakshi; Srinivas, D. (Catalysis Today, 2009)
Manganese complexes of 5,10,15,20-tetraphenylporphyrin (Mn(TPP)Cl) were grafted on SBA-15 functionalized with propyl-amine, -thiol and -sulfonic acid groups. The acido-basic properties of the support influenced the oxidation state, redox behavior and selective oxidation properties of the Mn complexes. Acidic supports (SBA-15-pr-SH and SBA-15-pr-SO(3)H) promoted the reduction of Mn ions in Mn-TPP complexes from 3+ to 2+ oxidation state. A similar behavior was found also when Mn(Salen)Cl complexes were immobilized on those supports. However, the extent of such facile reduction was more in the case of Mn-TPP than in Mn-Salen complexes. The former exhibited superior catalytic activity (turnover frequency) than the latter-type Mn complexes in regio-, stereo- and chemoselective oxidation of R-(+)-limonene with molecular oxygen (1 atm) at ambient temperatures. The catalytic oxidation activity correlates with the redox behavior of the grafted Mn complexes. (c) 2008 Elsevier B.V. All rights reserved.
18th National Symposium and Indo-US Seminar on Catalysis, Indian Inst Petroleum, Dehradun, INDIA, APR 16-18, 2007
Keywords: Grafted manganese complexes; Mn(Salen)Cl; Mn(TPP)Cl; Organo-functionalized SBA-15; Redox behavior of Mn; Selective oxidation of limonene

Regiospecific oxyhalogenation of aromatics over SBA-15-supported nanoparticle group IV-VI metal oxides - Saikia, Lakshi; Rajesh, M.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2010)
TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 exhibit efficient catalytic activity for oxyhalogenation of aromatics with the H(2)O(2)-halide ion system. Unlike the hitherto known solid catalysts, these reusable catalysts yield the para-halogenated product with 100% selectivity at 298 K and moderate acidic pH (3-5). The catalytic activity was enhanced by five orders of magnitude when supported on SBA-15.
Keywords: Haloperoxidase activity; Ordered mesoporous silica; Oxyhalogenation of aromatics; SBA-15; Supported metal oxides

Ultrasound-triggered release of ibuprofen from a chitosan-mesoporous silica composite - a novel approach for controlled drug release - Depan, Dilip; Saikia, Lakshi; Singh, Raj Pal (Macromolecular Symposia, 2010)
In this work, an attempt was made to synthesize a novel Chitosan-Mesoporous silica (CS-MS) hybrid composite to design a drug delivery system based on ultrasound triggered stimuli-responsive smart release. The in-vitro drug release properties of both the Mesoporous Silica (MS) and Chitosan (CS) hybrids were investigated. Ibuprofen (Ibu) was used as a model drug. The results from powder X-Ray diffraction (XRD) patterns, and BET N(2) adsorption isotherms exhibited that MS can accommodate drug molecules into the lumen of the channels and pores. Drug release, stimulated by temperature and pH of the release media was also investigated. We studied the Ultrasound (US) triggered release of Ibu in a simulated body fluid (pH 7.4). The results exhibited that US can be used as a non-invasive technique for drug release from polymeric materials. The enhancing effect of ultrasound on drug release is due to the Cavitation effect, without causing any significant destruction on the polymer morphology.
4th International Symposium on Macro-and Supramolecular Architectures and Materials, Dusseldorf, GERMANY, SEP 07-11, 2008
Keywords: Chitosan; drug delivery systems; ibuprofen; Mesoporous silica; Ultrasound

PD@SBA-15 Nanocomposite catalyst: synthesis and efficient solvent-free semihydrogenation of phenylacetylene under mild conditions - Bhuyan, Diganta; Selvaraj, Kaliaperumal; Saikia, Lakshi (Microporous and Mesoporous Materials, 2017)
Pd-0 nanoparticles (NPs) have been fabricated on SBA-15 using a facile, rapid and highly reproducible microwave-assisted reduction by solvent method. The as-synthesized Pd@SBA-15 nanocomposite was well characterized using low angle and wide angle XRD, TEM, FE-SEM, N-2 adsorption-desorption isotherm, FTIR, XPS etc. The Pd@SBA-15 nanocomposite act as an active, recyclable heterogeneous catalyst for semihydrogenation of phenylacetylene under solvent-free mild reaction conditions (303 K, atmospheric H-2). A maximum of 94.4% phenylacetylene conversion was achieved with very high selectivity for styrene (95.5%). Moreover, the used catalyst was recovered by centrifugation and reused up to four times without significant loss in their catalytic activity. This optimized reaction protocol for phenylacetylene was also well performed in case of various other alkynes with similar or better performance. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Pd-0 nanoparticles; Phenylacetylene; SBA-15; Semihydrogenation; Solvent-free